2009
DOI: 10.1021/ja904405v
|View full text |Cite
|
Sign up to set email alerts
|

Phase Space Prediction of Product Branching Ratios: Canonical Competitive Nonstatistical Model

Abstract: We present a new model for predicting branching ratios of chemical reactions when a branching of the reaction path occurs after the dynamical bottleneck, including the case where it occurs after an intermediate. The model is based on combining nonstatistical phase space theory for the direct component of a reaction with variational transition-state theory for an indirect component of reaction. The competition between direct and indirect processes is treated by an extension of the unified statistical model. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…29−35 For many of these reactions, it is found that conventional statistical theories of reaction, namely transition state theory (TST) and RRKM, 36 fail to predict isotope effects and, often more importantly, product selectivities. 37−39 Dynamical studies of nonstatistical reactions are reshaping our fundamental conceptions of mechanistic physical organic chemistry with profound significance in areas such as synthetic organic chemistry, 38 enzyme catalysis, 40 and reactive roaming.…”
Section: ■ Introductionmentioning
confidence: 99%
“…29−35 For many of these reactions, it is found that conventional statistical theories of reaction, namely transition state theory (TST) and RRKM, 36 fail to predict isotope effects and, often more importantly, product selectivities. 37−39 Dynamical studies of nonstatistical reactions are reshaping our fundamental conceptions of mechanistic physical organic chemistry with profound significance in areas such as synthetic organic chemistry, 38 enzyme catalysis, 40 and reactive roaming.…”
Section: ■ Introductionmentioning
confidence: 99%
“…25 In the “canonical competitive nonstatistical model” (CCNM), the branching between products is divided into “indirect” and “direct” components, the former being predicted from TST and the later predicted from phase space theory. The absence of an intermediate leads the CCNM model to allocate 100% of the reaction to the indirect component, which is dominated by the stability of the initially formed conformers of the products.…”
mentioning
confidence: 99%
“…1 and assuming a kinetically controlled mechanism, we can predict the most favorable isomers computationally [21,22]. Previous computational studies have also pointed out the fact that the final thermodynamically favored products might not reflect the selectivity of the kinetically favored hydroboration reactions [23] and emphasized the importance of dynamical effects beyond transition state theory [24][25][26].…”
Section: Monohydroboration Products Of Dienesmentioning
confidence: 91%